Dietary exposure to Arsenic, Cadmium, and lead amongst under-five Syrian refugee and Lebanese children in rural Lebanon - Sara Daher; Fouad Ziade; Moomen Baroudi (Food Chemistry Advances)
The adverse effects of toxic elements exposure are more intense among infants and children compared with adults. A cross-sectional study was conducted in 2019 among 743 Syrian refugee and Lebanese infant and young children in a rural area of North Lebanon (Akkar). Dietary assessment was conducted using the 24-hour dietary recall approach. Food products consumed by at least 10 % of the study population were identified (n = 12). Dietary exposure to arsenic, cadmium, and lead was assessed using the simple distribution approach with two scenarios: lower bound approach and upper bound approach; mean, 50th, 90th and 95th percentile exposure to toxic elements were calculated and compared to Health Based Guideline Values (HBGVs). Mean and 95th percentile dietary exposure of arsenic exceeded HBGVs, but not those for cadmium and lead which showed somewhat elevated exposure levels (reaching 78.5 %). Differences in dietary exposure between Syrian refugee and Lebanese infants and children were investigated and no significant differences were observed. Food products that contributed the most to toxic elements exposure were bread and infant formula among infants and bread and French fries among young children. Results observed in this study suggest the need for continuous toxic element dietary exposure monitoring of the studied groups.